Proceedings of the 4th International Conference on Web Intelligence, Mining and Semantics (WIMS14) 2014
DOI: 10.1145/2611040.2611097
|View full text |Cite
|
Sign up to set email alerts
|

Experiments with Emotion Contagion in Emergency Evacuation Simulation

Abstract: Multi-agent systems simulation is used to predict human behaviour in emergency evacuation cases. However, as human behaviour can change under the effect of emotions, it is essential to create models of artificial agents and simulations that mimic such behaviour in order to make prediction of the overall system performance. In emotional agents, the role of emotional contagion is important. Emotional contagion is a result of interaction between agents which could affect each others emotions. It is the case that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
6
0
4
Order By: Relevance
“…The functions f 1 (S (t), ν 1 (t)), f 2 (L(t), ν 2 (t)) and f 3 (I(t), ν 3 (t)) represent the actions of the control effort, where f 1 (S (t), ν 1 (t)) models the vaccination actions over susceptible individuals, f 2 (L(t), ν 2 (t)) describes the quarantine actions over latent individuals, and f 3 (I(t), ν 3 (t)) represents the treatment actions over infected individuals. Different mathematical descriptions for 6 …”
Section: Proposed Control Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The functions f 1 (S (t), ν 1 (t)), f 2 (L(t), ν 2 (t)) and f 3 (I(t), ν 3 (t)) represent the actions of the control effort, where f 1 (S (t), ν 1 (t)) models the vaccination actions over susceptible individuals, f 2 (L(t), ν 2 (t)) describes the quarantine actions over latent individuals, and f 3 (I(t), ν 3 (t)) represents the treatment actions over infected individuals. Different mathematical descriptions for 6 …”
Section: Proposed Control Strategiesmentioning
confidence: 99%
“…The largescale crowd evacuation is an important way for emergency responses of sudden disasters [3,4,5]. Many cases have shown that when panic emotions about accidents emerges in some individuals in the human population, their neighboring individuals tend to be infected through emotion contagion, resulting in devastating consequences in the human population in emergencies [6,7,8,9]. Currently, there are many definitions of emotion of individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reviewed and experimented with three emotional contagion models [15]. In this work, we use the ASCRIBE model [10], where the emotional effect of one agent to another generally depends on the expressiveness of the former, the openness of the latter, and the distance between the two.…”
Section: A Formal Representation Of Dimensional Theorymentioning
confidence: 99%